Performance of Free Software and Freeware in Telecommunication System - Farrukh Mirzaev; Khurshid Nematov (Journal La Multiapp, 2020)
This article discusses the Performance of Free Software and Freeware in Telecommunication System. Software or software is a special term for data that is digitally formatted and stored, including computer programs, their documentation, and various information that can be read and written by a computer. In other words, part of a computer system that is intangible. This term emphasizes the difference from computer hardware. Making the software itself requires a "programming language" written by the programmer which is then compiled with the compiler application so that it becomes code that can be recognized by the hardware machine.